THE ACTIVITY OF RHEUMATOID ARTHRITIS AND ITS THERAPY DURING PREGNANCY - Ergashova Madina Muxtorovna; Khusainova Munira Alisherovna; Toshtemirova Madina Oybekovna (Journals Park Publishing, 2024)
Rheumatoid arthritis (RA) often affects women of childbearing age, which determines a long-standing interest in studying the mutual effects of pregnancy and RA. In the first observation, described about 80 years ago, a decrease in the activity of the disease was noted in the absolute majority of pregnant women. In more recent prospective studies, it was shown that only 48-66% of pregnant women have clinical improvement during gestation, and postpartum exacerbation of RA is noted in 70% of patients, while most patients require drug therapy. The aim of the study was to evaluate the dynamics of RA activity according to DAS28–CRP during pregnancy and after childbirth; to clarify the effect of RA activity at the beginning of gestation on the further course of the disease. To determine the need for drug therapy in pregnant women with RA. Material and methods. Prospectively, in each trimester of gestation and for 12 months after delivery, it was followed 32 pregnancies in 29 women with reliable RA (ACR criteria of 1987) examined. Results and discussion. During pregnancy, 46% of RA patients had a decrease in disease activity. Within 12 months, on average 1.5 months after delivery, 75% of patients had an exacerbation of RA. In patients with remission and low disease activity at the beginning of pregnancy, RA activity during the entire gestation period and 1 month after delivery remained significantly lower than in patients with moderate and high activity in the first trimester (p=0.0008–0.04). A similar trend was observed in patients with no arthritis at the time of conception (according to the survey). 23 (71.9%) in patients with signs of disease activity during pregnancy, anti-inflammatory therapy was intensified, against which DAS28-CRP decreased (p=0.008), while in the remaining 9 (28.9%), with low activity without drug intervention, it tended to increase. After childbirth, patients with high and moderate activity improved earlier (p=0.008), since they resumed therapy with basic anti-inflammatory (HDL) and genetically engineered drugs earlier biological drugs (GIBP) than in patients with remission and low activity during pregnancy. In the latter, the tendency to increase activity persisted until 3 months after childbirth. In 12 (37.5%) patients who became pregnant while taking HDL or GIBP and urgently canceled them due to pregnancy, the disease activity in the I–III trimesters was significantly higher than in 20 (62.5%) cases when HDL and/or GIBP were not used or canceled in advance when planning pregnancy (p<0.04). Conclusions. Remission or low activity of RA at the beginning of pregnancy is a predictor of low activity of the disease and minimization of drug therapy up to complete rejection of it throughout pregnancy. Without medical intervention, RA activity may tend to increase. Postpartum exacerbation of RA is also noted in patients who had remission and low RA activity before childbirth. The abrupt cancellation of HDL or GIBP in connection with the onset of unplanned pregnancy contributes to an increase in the activity of RA already from the first trimester of gestation. Pregnancy should be planned by choosing stable anti-inflammatory therapy in advance.
Keywords: rheumatoid arthritis; pregnancy; rheumatoid arthritis activity; DAS28-CRP; anti-inflammatory therapy.